Experiences of patients with heart failure with medicines at transition intervention: Findings from the process evaluation of the Improving the Safety and Continuity of Medicines management at Transitions of care (ISCOMAT) programme. (31st July 2022) - Powell, Catherine; Ismail, Hanif; Davis, Maureen; Taylor, Andrew; Breen, Liz; Fylan, Beth; Alderson, Sarah L.; Gale, Chris P.; Kellar, Ian; Silcock, Jonathan; Alldred, David P.
Abstract: Background: Medicines are often suboptimally managed for heart failure patients across the transition from hospital to home, potentially leading to poor patient outcomes. The Improving the Safety and Continuity Of Medicines management at Transitions of care programme included: understanding the problems faced by patients and healthcare professionals; developing and co‐designing the Medicines at Transitions of care Intervention (MaTI); a cluster randomized controlled trial testing the effectiveness of a complex behavioural MaTI aimed at improving medicines management at the interface between hospitals discharge and community care for patients with heart failure; and a process evaluation. The MaTI included a patient‐held My Medicines Toolkit; enhanced communication between the hospital and the patient's community pharmacist and increased engagement of the community pharmacist postdischarge. This paper reports on the patients' experiences of the MaTI and its implementation from the process evaluation. Design: Twenty one‐to‐one semi‐structured patient interviews from six intervention sites were conducted between November 2018 and January 2020. Data were analysed using the Framework method, involving patients as co‐analysts. Interview data were triangulated with routine trial data, the Consolidated Framework for Implementation Research and a logic model. Results: Within the hospital setting patients engaged with the toolkit according to whether staff raised awareness of the My Medicines Toolkit's importance and the time and place of its introduction. Patients' engagement with community pharmacy depended on their awareness of the community pharmacist's role, support sources and perceptions of involvement in medicines management. The toolkit's impact on patients' medicines management at home included reassurance during gaps in care, increased knowledge of medicines, enhanced ability to monitor health and seek support and supporting sharing medicines management between formal and informal care networks. Conclusion: Many patients perceived that the MaTI offered them support in their medicines management when transitioning from hospital into the community. Importantly, it can be incorporated into and built upon patients' lived experiences of heart failure. Key to its successful implementation is the quality of engagement of healthcare professionals in introducing the intervention. Patient or Public Contribution: Patients were involved in the study design, as qualitative data co‐analysts and as co‐authors.